A cost-efficient algorithm for diagnosing children with dysmorphic features - Mariya Levkova; Milena Stoyanova; Mari Hachmeriyan; Lyudmila Angelova (Egyptian Journal of Medical Human Genetics, 2024)
Abstract It is crucial to create a cost-effective work protocol that will guide everyone involved in diagnosing children with dysmorphic features step-by-step and ensure that testing costs are reduced without compromising care quality in light of the rising prevalence of rare diseases and congenital malformations. Based on our own experience, we offer an effective approach for identifying children with dysmorphic traits. Following a thorough medical history and physical examination utilizing the dysmorphology checklist we created, the patient should have their photographs taken. The second step involves using face recognition software and searching dysmorphology databases for a matching diagnosis. The final two steps of the suggested protocol are ordering the molecular-genetic analysis and providing genetic counseling. The suggested approach could help in everyday practice and reduce unnecessary testing. It takes significant clinical expertise and knowledge to correctly diagnose a syndrome, especially the capacity to recognize the particular dysmorphic symptoms that can be typical for a given genetic disorder. The suggested dysmorphology checklist could be extremely helpful for routine daily practice.